2019
DOI: 10.1097/bsd.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Can the American College of Surgeons Risk Calculator Predict 30-Day Complications After Cervical Spine Surgery?

Abstract: Study Design: This was a retrospective cohort study. Objective: The objective of this study was to assess the American College of Surgeons (ACS) Risk Calculator’s ability to accurately predict complications after cervical spine surgery. Summary of Background Data: Surgical risk calculators exist in many fields and may assist in the identification of patients at increased risk for complications and readmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A study by McCarthy et al applied the calculator to a retrospective cohort of 237 lumbar and 404 cervical spine surgery patients and found no significant outcome prediction in the lumbar cohort. 26 This inability to detect a difference may have been due to an insufficient sample size, as the cervical cohort was able to significantly (P < 0.001) predict any complication as well as discharge to a skilled nursing facility. 26,27 The studies on spine surgery have been typically underpowered to demonstrate true efficacy of the ACS-NSQIP risk calculator at predicting postoperative outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study by McCarthy et al applied the calculator to a retrospective cohort of 237 lumbar and 404 cervical spine surgery patients and found no significant outcome prediction in the lumbar cohort. 26 This inability to detect a difference may have been due to an insufficient sample size, as the cervical cohort was able to significantly (P < 0.001) predict any complication as well as discharge to a skilled nursing facility. 26,27 The studies on spine surgery have been typically underpowered to demonstrate true efficacy of the ACS-NSQIP risk calculator at predicting postoperative outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…26 This inability to detect a difference may have been due to an insufficient sample size, as the cervical cohort was able to significantly (P < 0.001) predict any complication as well as discharge to a skilled nursing facility. 26,27 The studies on spine surgery have been typically underpowered to demonstrate true efficacy of the ACS-NSQIP risk calculator at predicting postoperative outcomes. However, there are several independent risk calculators being utilized that have showed promise in predicting spine surgery outcomes and can be used in conjunction with the risk calculator, or to further validate its usefulness in spine surgery.…”
Section: Discussionmentioning
confidence: 97%
“…McCarthy et al[ 22 ] found that the SRC predicted with a high degree of accuracy, the development of any complications, and discharge to nursing home (p<0.0001). They concluded that the SRC could not accurately predict specific complications in greater detail for these patients nor in cervical spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Since its conception, the accuracy of the ACS-NSQIP calculator in predicting outcomes has been investigated in many patient populations and procedures 14–21. To date, no study has been done to validate the ACS-NSQIP calculator in patients receiving surgical intervention for spinal metastases, despite previous work showing this calculator to be unreliable in other cancer types 22–24.…”
mentioning
confidence: 99%
“…[11][12][13] Since its conception, the accuracy of the ACS-NSQIP calculator in predicting outcomes has been investigated in many patient populations and procedures. [14][15][16][17][18][19][20][21] To date, no study has been done to validate the ACS-NSQIP calculator in patients receiving surgical intervention for spinal metastases, despite previous work showing this calculator to be unreliable in other cancer types. [22][23][24] Thus, the purpose of this study was to investigate the accuracy of the ACS-NSQIP surgical risk calculator in predicting postoperative outcomes in the metastatic spine disease population.…”
mentioning
confidence: 99%